PRINCIPIOS DE ASOCIATIVIDAD EN LA CORPORACION DE PRODUCTORES AGROPECUARIOS DE QUINSALOMA - Posligua Valle, Ricardo Moises (2018)
ssociativity is a cooperation strategy between companies, where each participating individual, maintaining their legal independence and managerial autonomy, voluntarily decides to participate in a joint effort with the other participants to search for a corporate objective. In the Canton Quinsaloma is COPAQ (Corporation of agricultural producers Quinsaloma) this organization has 145 members, each of them has production units of 1 to 50 has, with various crops such as rice, corn and soybeans, however, they allocate 34.67% for the cultivation of cocoa, which does not occur systematically, they only do so to sell the product immediately and use the money for subsistence or solve emerging needs. This